Beginning SQL Server 2008 for Developers - Dewson, Robin (Apress, 2012)
Beginning SQL Server 2008 for Developers is for those who see themselves as becoming developers, database administrators, or a mixture of both but have yet to tread that path with SQL Server 2008. Whether you have no knowledge of databases, have knowledge of desktop databases such as Microsoft Access, or even come from a server-based background such as Oracle, this book will provide you with the insight to get up and running with SQL Server 2008. Right from the start, this book will expand your basic knowledge, and you will soon find yourself moving from a beginner toward a competent and professional developer. This book aims to cater to a wide range of developers, from those who prefer to use a graphical interface for as much work as possible, to those who want to become more adept at using SQL Server 2008’s programming language, Transact SQL (T-SQL). Where practical, this book demonstrates, explains, and expands upon each method of using SQL Server 2008 so that you can evaluate which works best in your situation. This book contains plenty of examples that let you see how areas of SQL Server work and how you can apply the technology in your own work. You will learn the best way to complete a task, and you’ll even learn how to make the correct decision when presented with two or more choices. Once you reach the end of this book, you will be able to design and create solid and reliable database solutions competently and proficiently.